Environmental Impact Assessment and Siting of Filling Stations: Systematic Procedure in the Wa Municipality of Northern Ghana - Dangboor, Amatus; Agyemang, Isaac; Tampaah-Naah, Anthony (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2015)
The application of appropriate Environmental Impact Assessment (EIA) procedure on the various environmental categories is imperative for realizing quality and sustainable environment at all levels. This can be achieved through effective collaboration among the key actors or stakeholders and clear delineation of roles and responsibilities assigned to the respective players who are mandated to ensure the realization of this course. This study examines the application of EIA procedure on siting filling stations in Wa Municipal. The study engaged a mixed method design and used mainly interviews, observation and questionnaire in the collection of data. In findings; the research has established that there is no collective agreement among environmental institutions on the EIA procedure for filling stations projects. There is also low collaboration among these institutions especially at the technical committee level. The environmental institutions are confronted with a number of challenges in applying the EIA procedure on siting of filling stations in the Wa Municipality. Almost the entire municipality has not been zoned due to the expensive nature of schemes. Developers do fail to comply with the few schemes in suburbs that have them yet it has always been difficult to apply sanctions in the midst of political and socio-cultural interference. Key recommendations include: filling stations projects should be included in category A of environmental categories on which EIA are conducted considering the volatile nature and consequences on the environmental components, key environmental actors should strengthen the forms of collaboration to ensure effective application of the EIA procedure in filling stations construction